Growth Analysis of Three Soybean Varieties on Ultisol - Nugraha Ramadhan; Winda Purnama Sari; Dara Savitri; Eka Oktela Palja (Andalasian International Journal of Agriculture and Natural Sciences (AIJANS), 2023)
Expansion of planting areas by utilizing sub-optimal land and the use of superior varieties is one of the alternatives in increasing soybean production in Indonesia. Therefore, this study aims to analyze the growth of three soybean varieties on Ultisol land in the Experimental Garden of the Faculty of Agriculture, Andalas University. This activity was conducted from September to November of 2022. The soybean varieties used in this study were Dena 1, Devon 1, and Demas 1. This research was designed using a Randomized Group Design with 1 factor, namely the type of variety with 3 groups of replications. The observation results of each treatment were analyzed statistically. If F count is greater than F table, then continued with Tukey's Further Test at the 5% level. It was concluded that some of the observed characters of the three soybean varieties showed that there were significant differences in growth in the observation of plant height and leaf area index. While in the observation of plant growth rate and the ratio of crown: root there was no significant difference between the tested varieties.